Suppressing Erosion and N (Nitrogen) Nutrients Loss Using Polyacrylamide under Sweet Corn Cultivation Under Climate Change Issue - Yuliana Eva Agasi; Niken Ida Lovita; Dwi Rustam Kendarto; Ali Rahmat (Indonesian Journal of Limnology, 2023)
Climate change is currently a significant issue that poses a threat to the environment. Climate change can trigger increased rainfall, which promotes erosion in many areas. Erosion can lead to the depletion of nutrients in the soil, ultimately reducing the availability of nutrients for plants and causing a decline in land productivity. This can result in widespread land degradation. To avoid this risk soil conservation is needed. Soil conservation can be done to increase land productivity with chemical methods, such as using soil amendments with polyacrylamide (PAM). PAM is an anionic polymer-based material that can improve soil aggregate stability, infiltration rate, and suppress erosion. The purpose of this study is to determine the effect of PAM on erosion suppression, the loss of N nutrients, and on the growth of sweet corn plants. The results of the analysis showed that there is an effect of PAM on the suppression of erosion and loss of N nutrients in the soil. The dose of PAM of 60 kg/ha was able to suppress erosion by 53.16% and reduce the loss of nutrients N by 15.07%. The most optimal and efficient dose in optimizing sweet corn plant growth is 15 kg/ha.